Psychosocial interventions for self‐harm in adults - Witt, Katrina G (Cochrane Database Syst Rev, 2021)
BACKGROUND: Self‐harm (SH; intentional self‐poisoning or self‐injury regardless of degree of suicidal intent or other types of motivation) is a growing problem in most counties, often repeated, and associated with suicide. There has been a substantial increase in both the number of trials and therapeutic approaches of psychosocial interventions for SH in adults. This review therefore updates a previous Cochrane Review (last published in 2016) on the role of psychosocial interventions in the treatment of SH in adults. OBJECTIVES: To assess the effects of psychosocial interventions for self‐harm (SH) compared to comparison types of care (e.g. treatment‐as‐usual, routine psychiatric care, enhanced usual care, active comparator) for adults (aged 18 years or older) who engage in SH. SEARCH METHODS: We searched the Cochrane Common Mental Disorders Specialised Register, the Cochrane Library (Central Register of Controlled Trials [CENTRAL] and Cochrane Database of Systematic reviews [CDSR]), together with MEDLINE, Ovid Embase, and PsycINFO (to 4 July 2020). SELECTION CRITERIA: We included all randomised controlled trials (RCTs) comparing interventions of specific psychosocial treatments versus treatment‐as‐usual (TAU), routine psychiatric care, enhanced usual care (EUC), active comparator, or a combination of these, in the treatment of adults with a recent (within six months of trial entry) episode of SH resulting in presentation to hospital or clinical services. The primary outcome was the occurrence of a repeated episode of SH over a maximum follow‐up period of two years. Secondary outcomes included treatment adherence, depression, hopelessness, general functioning, social functioning, suicidal ideation, and suicide. DATA COLLECTION AND ANALYSIS: We independently selected trials, extracted data, and appraised trial quality. For binary outcomes, we calculated odds ratio (ORs) and their 95% confidence intervals (CIs). For continuous outcomes, we calculated mean differences (MDs) or standardised mean differences (SMDs) and 95% CIs. The overall quality of evidence for the primary outcome (i.e. repetition of SH at post‐intervention) was appraised for each intervention using the GRADE approach. MAIN RESULTS: We included data from 76 trials with a total of 21,414 participants. Participants in these trials were predominately female (61.9%) with a mean age of 31.8 years (standard deviation [SD] 11.7 years). On the basis of data from four trials, individual cognitive behavioural therapy (CBT)‐based psychotherapy may reduce repetition of SH as compared to TAU or another comparator by the end of the intervention (OR 0.35, 95% CI 0.12 to 1.02; N = 238; k = 4; GRADE: low certainty evidence), although there was imprecision in the effect estimate. At longer follow‐up time points (e.g., 6‐ and 12‐months) there was some evidence that individual CBT‐based psychotherapy may reduce SH repetition. Whilst there may be a slightly lower rate of SH repetition for dialectical behaviour therapy (DBT) (66.0%) as compared to TAU or alternative psychotherapy (68.2%), the evidence remains uncertain as to whether DBT reduces absolute repetition of SH by the post‐intervention assessment. On the basis of data from a single trial, mentalisation‐based therapy (MBT) reduces repetition of SH and frequency of SH by the post‐intervention assessment (OR 0.35, 95% CI 0.17 to 0.73; N = 134; k = 1; GRADE: high‐certainty evidence). A group‐based emotion‐regulation psychotherapy may also reduce repetition of SH by the post‐intervention assessment based on evidence from two trials by the same author group (OR 0.34, 95% CI 0.13 to 0.88; N = 83; k = 2; moderate‐certainty evidence). There is probably little to no effect for different variants of DBT on absolute repetition of SH, including DBT group‐based skills training, DBT individual skills training, or an experimental form of DBT in which participants were given significantly longer cognitive exposure to stressful events. The evidence remains uncertain as to whether provision of information and support, based on the Suicide Trends in At‐Risk Territories (START) and the SUicide‐PREvention Multisite Intervention Study on Suicidal behaviors (SUPRE‐MISS) models, have any effect on repetition of SH by the post‐intervention assessment. There was no evidence of a difference for psychodynamic psychotherapy, case management, general practitioner (GP) management, remote contact interventions, and other multimodal interventions, or a variety of brief emergency department‐based interventions. AUTHORS' CONCLUSIONS: Overall, there were significant methodological limitations across the trials included in this review. Given the moderate or very low quality of the available evidence, there is only uncertain evidence regarding a number of psychosocial interventions for adults who engage in SH. Psychosocial therapy based on CBT approaches may result in fewer individuals repeating SH at longer follow‐up time points, although no such effect was found at the post‐intervention assessment and the quality of evidence, according to the GRADE criteria, was low. Given findings in single trials, or trials by the same author group, both MBT and group‐based emotion regulation therapy should be further developed and evaluated in adults. DBT may also lead to a reduction in frequency of SH. Other interventions were mostly evaluated in single trials of moderate to very low quality such that the evidence relating to the use of these interventions is inconclusive at present.